Ontogeny of gonadotrophin-inhibitory hormone in the cichlid fish Cichlasoma dimerus - Di Yorio, María Paula (2018)
RFamide peptides are expressed in the early stages of development in most vertebrates. Gonadotrophin-inhibitory hormone (GnIH) belongs to the RFamide family, and its role in reproduction has been widely studied in adult vertebrates, ranging from fish to mammals. Because only 3 reports have evaluated GnIH during development, the present study aimed to characterise the ontogeny of GnIH in the fish model Cichlasoma dimerus. We detected the presence of 2 GnIH-immunoreactive (-IR) cell clusters with spatial and temporal differences. One cluster was observed by 3 days post-hatching (dph) in the nucleus olfacto-retinalis (NOR) and the other in the nucleus posterioris periventricularis by 14 dph. The number of GnIH-IR neurones increased in both nuclei, whereas their size increased only in the NOR from hatchling to juvenile stages. These changes occurred from the moment that larvae started feeding exogenously and during development and differentiation of gonadal primordia. We showed by double-label immunofluorescence that only GnIH-IR neurones in the NOR co-expressed gonadotrophin-releasing hormone 3 associated peptide. In addition, GnIH-IR fibre density increased in all brain regions from 5 dph. GnIH-IR fibres were also detected in the retina, optic tract and optic tectum, suggesting that GnIH acts as a neuromodulator of photoreception and the integration of different sensory modalities. Furthermore, there were GnIH-IR fibres in the pituitary from 14 dph, which were in close association with somatotrophs. Moreover, GnIH-IR fibres were observed in the saccus vasculosus from 30 dph, suggesting a potential role of GnIH in the modulation of its function. Finally, we found that gnih was expressed from 1 dph, and that the pattern of variation of its transcript levels was in accordance with that of cell number. The results of the present study comprise a starting point for the study of new GnIH roles during development.